Identifying and Understanding the Health Information Experiences and Preferences of Individuals With TBI, SCI, and Burn Injuries. (September 2016) - Coffey, Nathan T; Weinstein, Ali A; Cai, Cindy; Cassese, Jimmy; Jones, Rebecca; Shaewitz, Dahlia; Garfinkel, Steven
Introduction: Traumatic brain injury, spinal cord injury, and burn injury can cause lifelong disability and changes in quality of life. In order to meet the challenges of postinjury life, various types of health information are needed. We sought to identify preferred sources of health information and services for persons with these injuries and discover how accessibility could be improved. Methods: Thirty-three persons with injury participated in semistructured interviews. Responses to interview questions were coded using NVivo. Results: Participants' difficulties accessing health information varied by injury type and individually. The majority of respondents found information via the Internet and advocated its use when asked to describe their ideal health information system. Nearly all participants supported the development of a comprehensive care website. When searching for health information, participants sought doctor and support group networks, long-term health outcomes, and treatments specific to their injury. Conclusion: To optimize the quality of health information resources, Internet-based health-care platforms should add or highlight access points to connect patients to medical professionals and support networks while aggregating specialized, injury-specific research and treatment information.